2013
DOI: 10.1186/1743-422x-10-90
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HCV genotypes in district Mardan

Abstract: BackgroundApproximately 170 million people are infected with Hepatitis C virus (HCV) worldwide. The prevalence of chronic HCV infections in Pakistan is about 5%, with most individuals being infected with HCV genotype 3a. Data on HCV genotypes distribution across various districts of the country are scarce. One example is district Mardan from where such data is available only from 17 individuals. Accordingly, the present study aimed at determining HCV genotypes distribution among 177 HCV RNA positive individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
12
24
2
Order By: Relevance
“…This study ascertained that HCV genotypes were spread with equal probability between the both sexes and there was no association between gender and HCV genotypes. These results are in agreement with multiple previous studies indicating little statistical association between genders and genotypes in Pakistan (8,(10)(11)(12). This study contradicts a Libyan study that showed the association of various HCV genotypes with gender (13).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This study ascertained that HCV genotypes were spread with equal probability between the both sexes and there was no association between gender and HCV genotypes. These results are in agreement with multiple previous studies indicating little statistical association between genders and genotypes in Pakistan (8,(10)(11)(12). This study contradicts a Libyan study that showed the association of various HCV genotypes with gender (13).…”
Section: Discussionsupporting
confidence: 94%
“…This study also reported many rare genotypes like 5a, 1c, and 6a, which are uncommon and less reported. Unlike Ali et al (8) sudy findings, the findings of this study support the verdict of some previous studies that showed the presence of genotypes such as 5a, 4a, and 1c in spite of their rare status (9)(10)(11)16). These findings are in contradiction with those of some studies that have shown the partial absence of genotypes 4, 5, and 6 (8,17).…”
Section: Discussioncontrasting
confidence: 86%
“…The frequency of HCV is highest in few countries and areas, such as in Europe 25 million cases are HCV positive [17]. In Pakistan, HCV is 5% prevalent [18], whereas 5-9% prevalence is detected in Khyber Pakhtunkhwa province of Pakistan [19] causing liver cancer [20]. HCV-4 is prevalent among Middle East and Africa causing more than 80% of HCV infections and has recently spread to several European countries.…”
Section: Frequency Of Hcv Genotypes and Infectionsmentioning
confidence: 99%
“…On the other hand, genotype 3a and 1b are more prevalent in Iran, Pakistan and India (20). Patients with HCV genotype 3a are found to be at an accelerated risk of steatosis and hepatic fibrosis whereas, severe liver disease has been reported in patients with chronic HCV genotype 1b (21).…”
Section: Epidemiologymentioning
confidence: 99%